2005
DOI: 10.1897/04-409r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory culture and life-cycle experiments with the benthic amphipod melita plumulosa (zeidler)

Abstract: In Australia, the collection of estuarine invertebrates from the field for whole-sediment toxicity tests is hindered because of temporal variability in their population densities and distributions. The present study aimed to develop culturing procedures for Melita plumulosa (Zeidler), an epibenthic and intertidal, deposit-feeding amphipod that is native to the southeastern coast of Australia. During a 28-d chronic exposure, the species was tested under a range of salinities (5-35 per thousand), temperatures (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…Melita plumulosa were obtained from laboratory-maintained cultures originally established from organisms collected from intertidal mud flats at Brooklyn in the Hawkesbury River, north of Sydney. Procedures for maintaining cultures of M. plumulosa in the laboratory have been described previously (Hyne et al 2005). Tellina deltoidalis of 5 to 8 mm in length were collected during low tide from mud flats at Boronia Park, Lane Cove River, Sydney, Australia, during 2002 and 2003.…”
Section: Methodsmentioning
confidence: 99%
“…Melita plumulosa were obtained from laboratory-maintained cultures originally established from organisms collected from intertidal mud flats at Brooklyn in the Hawkesbury River, north of Sydney. Procedures for maintaining cultures of M. plumulosa in the laboratory have been described previously (Hyne et al 2005). Tellina deltoidalis of 5 to 8 mm in length were collected during low tide from mud flats at Boronia Park, Lane Cove River, Sydney, Australia, during 2002 and 2003.…”
Section: Methodsmentioning
confidence: 99%
“…Sediment from the surface layer (top 2-4 cm) was scooped into two clean Zip-lock 1 bags using a clean stainless steel shovel, the bags were sealed, and the sediment was stored in a cool room for a maximum of 2 months before use. This sediment has been characterized in the past and found to contain relatively low sediment-bound and porewater contaminant concentrations and has been deemed suitable for culturing M. plumulosa [18,19].…”
Section: Test Mediamentioning
confidence: 99%
“…The lids of the test vessels were loosely capped and aerated by continuously bubbling air (a tube was inserted through the lid into the test solution). The amphipods were fed small amounts of fish food (0.03 mg per amphipod, Sera Micron) at the start of the test and after each water change to prevent organism death resulting from starvation or stress [16,18]. The pH, salinity, temperature, and dissolved oxygen were measured at the start and end of each test and during each water change ($72 h).…”
Section: Toxicity Test Proceduresmentioning
confidence: 99%
“…Males are readily distinguishable from females by their larger gnathopod 2 as well as having more bristles along the antennae . Optimal culture conditions for this amphipod as established by Hyne et al (2005) are seawater of 25‰ salinity at 25°C ambient temperature on sediment composed of > 96% silt.…”
Section: Biology Of Melita Plumulosamentioning
confidence: 99%
“…Studies have demonstrated this amphipod to be sensitive to both aqueous and sediment-bound metals and PAHs in both acute and chronic exposures, with juvenile animals displaying greater sensitivity than adult M. plumulosa Hyne et al, 2005;King et al, 2005Spadaro et al, 2008).…”
Section: Ecotoxicology Of Melita Plumulosamentioning
confidence: 99%